SO2 and NO emissions during combustion of high-alkali coal over a wide temperature range: Effect of Na species and contents. (1st February 2022) - Zhang, Zhikun; Tang, Mingtu; Yang, Ziyan; Ma, Jiao; Liu, Lina; Shen, Boxiong
Highlights: Effects of Na on SO2 /NO emissions over a wide temperature range were studied. Sodium species and contents played an important role in the conversion of S/N. The migration and release of Na and S in ash at 900–1400 °C was studied. The fixation effect of sodium on sulfur in coal ash was revealed. Abstract: High-alkali Zhundong coal (ZDc) provides the main energy supply in China due to its abundant reserves and high quality. However, its high alkali contents cause a series of ash-related problems (fouling, slagging, and corrosion, etc.) in the dry bottom boiler. In recent years, a slag-tap cyclone-fired boiler operated at higher temperatures has attracted extensive attentions in China, due to its potential in alleviating the ash-related problems. However, its emission characteristics of SO2 and NO are rarely reported. In this study, therefore, the effects of alkali species and contents on SO2 and NO emissions during the combustion of high-alkali coal in a wide temperature range of 200–1400 °C were investigated. NaCl and Na2 CO3 were selected as the representative alkali species and loaded on ZDc with different contents of 0.5, 1.5, and 3.0 wt%. The results demonstrated that the addition of both Na species contributed to the reduction of SO2 and NO emission amounts significantly, as well as the shift of their maximum emission temperatures to lower temperatures. The suppression effect of Na on SO2 at low temperature stage was improved as increasing the loading amount of Na species from 0.5 to 3.0 wt%. However, the suppression effect of Na on SO2 at high temperature stage gradually decreased due to the instability of the formed Na-containing sulfates and further release of SO2 . Na species showed a negligible effect on the thermal NO emission at high temperature of above 1300 °C, and the highest suppression effect of NO was achieved at a Na loading amount of 1.5 wt%. It is noteworthy that Na2 CO3 was more effective in the suppression of SO2 and NO emissions than NaCl. In addition, it was found that the addition of both NaCl and Na2 CO3 increased the S content in the ash, indicating that the increase of sodium content in the coal could improve the sulfur fixation effect of coal ash. Besides, the enhanced XRD diffraction intensity of Na2 SO4 and Na6 Ca2 Al6 Si6 O24 (SO4 )2 in Na-loaded ash further proved the promoted sulfur fixation effect by sodium addition.